Thomasʼ calculus early transcendentals Eleventh edition - Tomas, George B; Giordano, Frank R; Hass, Joel; Weir, Mauice D (Boston, USA Pearson addison wesley, 2008)
This is a special international edition of an esablished title widely used by colleges and universites throughout the world. Pearson Education international published this special edition for the benefit of students outside the USA and canda
Media Upgrade
Not for sale in the USA or Canda
Keywords: Mathematician; Set theory